Novel therapeutic Strategies for Targeting Liver Cancer Stem Cells - Naoki Oishi; Xin Wei Wang (2011)
The cancer stem cell (CSC) hypothesis was first proposed over 40 years ago.Advances in CSC isolation were first achieved in hematological malignancies, with the first CSC demonstrated in acute myeloid leukemia.However, using similar strategies and technologies, and taking advantage of available surface markers, CSCs have been more recently demonstrated in a growing range of epithelial and other solid organ malignancies, suggesting that the majority of malignancies are dependent on such a compartment.Primary liver cancer consists predominantly of hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC).It is believed that hepatic progenitor cells (HPCs) could be the origin of some HCCs and ICCs.Furthermore, stem cell activators such as Wnt/-catenin, TGF-, Notch and Hedgehog signaling pathways also expedite tumorigenesis, and these pathways could serve as molecular targets to assist in designing cancer prevention strategies.Recent studies indicate that additional factors such as EpCAM, Lin28 or miR-181 may also contribute to HCC progression by targeting HCC CSCs.Various therapeutic drugs that directly modulate CSCs have been examined in vivo and in vitro.However, CSCs clearly have a complex pathogenesis, with a considerable crosstalk and redundancy in signaling pathways, and hence targeting single molecules or pathways may have a limited benefit for treatment.Many of the key signaling molecules are shared by both CSCs and normal stem cells, which add further challenges for designing molecularly targeted strategies specific to CSCs but sparing normal stem cells to avoid side effects.In addition to the direct control of CSCs, many other factors that are needed for the maintenance of CSCs, such as angiogenesis, vasculogenesis, invasion and migration, hypoxia, immune evasion, multiple drug resistance, and radioresistance, should be taken into consideration when designing therapeutic strategies for HCC.Here we provide a brief review of molecular signaling in liver CSCs and present insights into new therapeutic strategies for targeting liver CSCs.